2011
DOI: 10.4314/njp.v38i3.72271
|View full text |Cite
|
Sign up to set email alerts
|

Rate of isolation of streptococcus species from children with bacterial infections: an indication for introduction of streptococcal vaccines

Abstract: Version 3.5.1. Statistical significance was set at p < 0.05.A total of 2,247 samples were received during the study period. Of the 1,242 bacteria isolated, 502 (40.4%) were , 232 (18.7%) were and 146 (11.8%) were Streptococcus species: 78 were isolated from blood, 9 from sputum, 11 from throat swabs and 28 from other sites while urine and eye swabs had 10 each. One hundred and six (72.6%) of the streptococci were from children aged 5 years and below. Most of the Streptococci (88.1%) were untyped. Among the 17 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Some members of the normal flora produce antibacterial chemicals (bacteriocins) as a side product of their metabolism, thus generating a local antibiotic effect which hinders the invader (The Crohnie, htt://primer.crohn.ie/ human-normal-flora). Streptococcal infection has been identified as an important cause of severe disease in Nigeria (Onalo et al, 2011). Ceftriaxone 30 22 0 0 100 Ceftazidime 30 22 0 0 100 Cefuroxime 30 22 0 0 100 Erythromycin 30 22 0 0 100 Cotrimoxazole 25 18 4 18 82 Ampicillin 30 22 0 0 100 Tetracycline 30 15 7 32 68 Record are however scanty on characterization of streptococcal species in bacterial infections in Nigeria (Onalo et al, 2011).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Some members of the normal flora produce antibacterial chemicals (bacteriocins) as a side product of their metabolism, thus generating a local antibiotic effect which hinders the invader (The Crohnie, htt://primer.crohn.ie/ human-normal-flora). Streptococcal infection has been identified as an important cause of severe disease in Nigeria (Onalo et al, 2011). Ceftriaxone 30 22 0 0 100 Ceftazidime 30 22 0 0 100 Cefuroxime 30 22 0 0 100 Erythromycin 30 22 0 0 100 Cotrimoxazole 25 18 4 18 82 Ampicillin 30 22 0 0 100 Tetracycline 30 15 7 32 68 Record are however scanty on characterization of streptococcal species in bacterial infections in Nigeria (Onalo et al, 2011).…”
Section: Resultsmentioning
confidence: 99%
“…Streptococcal infection has been identified as an important cause of severe disease in Nigeria (Onalo et al, 2011). Ceftriaxone 30 22 0 0 100 Ceftazidime 30 22 0 0 100 Cefuroxime 30 22 0 0 100 Erythromycin 30 22 0 0 100 Cotrimoxazole 25 18 4 18 82 Ampicillin 30 22 0 0 100 Tetracycline 30 15 7 32 68 Record are however scanty on characterization of streptococcal species in bacterial infections in Nigeria (Onalo et al, 2011). In a study of Streptococcal species identification of bacterial infection in Abuja (Nigeria), the researchers reported that 58.8% (10 out of 17 isolates of Streptococcus typed) of streptococcal infection were caused by Streptococcus pneumoniae (Onalo et al, 2011).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation